Consequences of Proton Acceleration in Blazar Jets - Mastichiadis, Apostolos (2016)
Hadronic models of blazar emission constitute an interesting alternative to the more popular leptonic ones. Using the BL Lac object Mrk 421 as a characteristic example, we present two distinct ways of modeling the spectral energy distribution of blazars in the hadronic context, and we discuss the predictions of each variant on the spectral shape, the multi-wavelength variability, the cosmic-ray flux, and the high-energy neutrino emission. Focusing on the latter, we then present an application of the hadronic model to individual BL Lacs that were recently suggested to be the counterparts of some of the IceCube neutrinos.